The serine protease HtrA1 is a novel prognostic factor for human mesothelioma. (August 2008) - Baldi, Alfonso; Mottolese, Marcella; Vincenzi, Bruno; Campioni, Mara; Mellone, Pasquale; Di Marino, Mariapia; di Crescenzo, Vincenzo G; Visca, Paolo; Menegozzo, Simona; Spugnini, Enrico P; Citro, Gennaro; Ceribelli, Anna; et al.
Aims: The objective of our study was to analyze the potential prognostic value of the expression of the serine protease HtrA1 and of EGFR in 70 malignant mesotheliomas.Materials & methods: Immunohistochemistry was used to determine the expression of HtrA1 and EGFR. Univariate and multivariate analyses were used to correlate expression of these molecular factors in combination with available clinicopathologic data to patient survival.Results: A positive, statistically significant relationship has been recorded between HtrA1 expression level and survival (p < 0.0001). By contrast, a negative relationship has been identified between EGFR expression and survival (p = 0.02). Moreover, extension of the tumor (T) and involvement of lymph nodes (N) advanced status (p = 0.001 and 0.002, respectively), as well as the sarcomatoid histotype (p = 0.005), correlated significantly with poor survival. Finally, by a multivariate Cox regression analysis, the only immunohistochemical parameter that resulted to influence overall survival was HtrA1 (p = 0.0001). Interestingly, the prognostic value of HtrA1 expression was completely independent from EGFR expression (p < 0.0001).Conclusion: This is the first study of the relationship between HtrA1 expression and survival of mesothelioma patients. The data obtained strongly indicate the utilization of HtrA1 expression as a prognostic parameter for mesothelioma and suggest this serine protease as a possible molecular target for the treatment of malignant mesotheliomas.